An improved method to synthesize nanoscale graphene oxide using much less acid. (June 2019) - Luo, D.; Zhang, F.; Ren, Z.; Ren, W.; Yu, L.; Jiang, L.; Ren, B.; Wang, L.; Wang, Z.; Yu, Y.; Zhang, Q.; Ren, Z.
Abstract: Because graphene oxide is so important for many applications and also the precursor for large quantity of graphene, a low cost and environmentally friendly method using much less acid is essential to the future of graphene oxide and graphene. It is a great challenge to reduce the acid usage to avoid the safety risk, but tremendous benefits could be achieved if this were made possible for the industrial-scale synthesis of graphene oxide and graphene. In this work, we report a fast and simple method that uses much less acid than the state of the art to obtain nanoscale graphene oxide by using the heat released by the reaction. With the introduction of dry ice, the reaction temperature can be well controlled, thus stabilizing the highly oxidative and explosive Mn2 O7 intermediate in order to avoid safety risk. Graphical abstract: Image 1 Highlights: A fast, simple, and less acid method to synthesize nanoscale graphene oxide has been reported in this work. The adding of dry ice stabilizes reactive intermediates and helps the reaction in a good control with a two-step manner. The less requirement of acid by this method largely reduces the cost of wastewater treatment and environmental impact.